Monoclinic WO3 nanorods-rutile TiO2 nanoparticles core-shell interface for efficient DSSCs - Shaikh, ShoyebMohamad F.; Kalanur, Shankara S.; Mane, Rajaram S.; Joo, Oh-Shim (ROYAL SOC CHEMISTRY, 2013)
A core-shell photoanode, composed of a monoclinic WO3 nanorods core encapsulated with a rutile TiO2 nanoparticles shell, reveals similar to 246% enhancement in power conversion efficiency due to improved current density and open circuit voltage values and longer-lived charge carriers.
Keywords: SENSITIZED SOLAR-CELLS; PHOTOELECTROCHEMICAL ACTIVITY; TUNGSTEN TRIOXIDE; OXIDE FILMS; DEPOSITION; CONSTANTS; HYBRID; LAYERS